2021
DOI: 10.5539/elt.v14n2p20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the ADDIE Model within an E-Learning Environment in Developing Creative Writing in EFL Students

Abstract: The present research aimed to examine the effectiveness of the ADDIE model as used in teaching online in the LMS of Blackboard® and its facilities such as discussion boards, forums and blogs for improving the creative writing skills of EFL college students. The researcher utilized a quasi-experimental method, involving a pretest, posttest and control group design. Sixty students were randomly selected from freshmen studying in the English department participated in the study and were assigned equally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 23 publications
3
46
0
12
Order By: Relevance
“…Furthermore, the findings also showed that the learners very positively perceived BBCB as a platform for English learning. These findings are consistent with previous research on learners’ attitudes to and perceptions of BB use in the Saudi context ( Almekhlafy, 2020 ; Elzainy et al, 2020 ; Almelhi, 2021 ). Due to the platform’s multimodal capabilities, and its features that are easy to use, and time-saving, BBCB created a perfect virtual zone where the students could feel comfortable while learning.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the findings also showed that the learners very positively perceived BBCB as a platform for English learning. These findings are consistent with previous research on learners’ attitudes to and perceptions of BB use in the Saudi context ( Almekhlafy, 2020 ; Elzainy et al, 2020 ; Almelhi, 2021 ). Due to the platform’s multimodal capabilities, and its features that are easy to use, and time-saving, BBCB created a perfect virtual zone where the students could feel comfortable while learning.…”
Section: Discussionsupporting
confidence: 92%
“…ADDIE Model is the model used in this research to develop the Encyclopedia of Art, Culture, and Tourism in Palembang. It has five stages of research, namely, Analysis, Design, Development, Implementation, and Evaluation (Almelhi, 2021;Budoya et al, 2019;Widyastuti & Susiana, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…After that, they are given a questionnaire form to fill which will then be used as a reference by the research team. • Evaluation phase: weighing the effectiveness of the end product, tools and activities, investigating acheivements regarding the initial objectives, assessing the impact(s) of the end product, identifying and modifying what can be improved from the end product (Almelhi, 2021;Budoya et al, 2019;Cahyadi, 2019) (Almelhi, 2021;Budoya et al, 2019;Cahyadi, 2019;Sesmiyanti et al, 2021). (The evaluation phase is an overall evaluation of the product after it went through a series of meticulous field tests in the previous phase, namely one-to-one expert, one-to-one learner, small group, and large group tests).…”
Section: Evaluation Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Prosedur penelitian dan pengembangan berorientasi pada pembaharuan terhadap suatu produk melalui validasi hingga uji coba untuk menjamin 9 H. Mubarok kualitas produk yang dihasilkan 14 . Pada model penelitian dan pengembangan ini menggunakan model ADDIE dengan prosedur tahapan 1) Analysis; 2) Design; 3) Develop; 4) Implementation; and 5) Evaluation 15 . Pemilihan model pengembangan ADDIE berdasarkan pada struktur prosedur yang sistematis sehingga relevan dengan pengembangan buku ajar digital 16 .…”
Section: Metode Penelitianunclassified